2016
DOI: 10.1556/0806.43.2015.047
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality Evaluation of Direct Seeded Basmati Rice (Oryza sativaL.) under Different Irrigation and Nitrogen Regimes

Abstract: Management practices need to be developed for successful cultivation of good quality aerobic basmati rice. Field experiments were conducted at Ludhiana, India during the summer seasons of 2011 and 2012 to ascertain the optimum irrigation schedule and dose and timings of nitrogen application to direct seeded basmati rice cultivar Pusa Basmati 1121. Three irrigation schedules (irrigations at 30, 50 and 70 mm CPE), three nitrogen levels (40, 60 and 80 kg N ha -1 ) and two modules of nitrogen splits (3 splits, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…The addition of N doses through Vermi-compost from 10 to 30 kg/ha in succession resulted in a decrease in the spike length (12.6-11.2 cm), spikes m-2 (377.1-339.1), and 1000-grain weight (41.0-40.3 g). Similar findings have been reported by Mattas, et al [9], [10]; Mumtazet al [11].…”
Section: Test Weightsupporting
confidence: 92%
“…The addition of N doses through Vermi-compost from 10 to 30 kg/ha in succession resulted in a decrease in the spike length (12.6-11.2 cm), spikes m-2 (377.1-339.1), and 1000-grain weight (41.0-40.3 g). Similar findings have been reported by Mattas, et al [9], [10]; Mumtazet al [11].…”
Section: Test Weightsupporting
confidence: 92%
“…However, a deep water table might lead to poor root growth, which affects the uptake of micro-and trace elements [46] and even leads to crop lodging at the grain filling stage [59], thus leading to reduced rice grain quality. Optimized water management may improve rice milling quality, if it is implemented correctly [60] or when an optimized N management is being used [61,62]. Liu et al (2008) indicated that alternate wetting and drying irrigation could enhance activities of some enzymes and decrease ethylene production in grains in middle and late grain filling stages, while the situation was reversed under extreme alternate wetting and drying or severe soil drying, which might be the primary physiological mechanism of good quality for optimized water management [60].…”
Section: Rice Grain Quality Improvement In Integrated Rice Management...mentioning
confidence: 99%
“…21 and 42 DAS to 3splits i.e., 21, 42 and 63 DAS) with 40 kg N ha -1 had no influence on grain yield in contrast to increasing splits (2 to 3 splits) with 60 kg N ha -1 which resulted in significantly higher grain yield than 2 splits. In another study conducted at Ludhiana, Kaur et al (2016) found that two modules of N splits [3 splits, i.e. application at 3, 6 and 9 weeks after sowing (WAS) and 4 splits, i.e.…”
Section: Effect Of Nitrogen Schedules On Crop Productivitymentioning
confidence: 99%
“…The grain quality parameters like hulling %, milling %, head rice recovery, L/B ratio and amylose content were analysed and most of the characters were found to be remained unaffected due to nitrogen management practices, except milling percentage and head rice recovery which were found to be statistically superior when N was applied in four equal amounts at early tillering, active tillering, panicle initiation and panicle emergence (Chaudhary et al, 2011). In a study conducted on DSBR cultivar "Pusa Basmati 1121" at Ludhiana, Kaur et al (2016) found that various parameters viz., hulled (brown), milled and head rice recovery, hl weight, L/B ratio, protein, amylose and amylopectin content as well as the cooking quality were not affected by two modules of N splits (3 splits, i.e. application at 3, 6 and 9 WAS and 4 splits, i.e.…”
Section: Effect Of Nitrogen Schedules On Quality Of Ricementioning
confidence: 99%